Women's knowledge and attitudes to the menopause: a comparison of women over 40 who were in the perimenopause, post menopause and those not in the peri or post menopause - Bisma Tariq; Samantha Phillips; Rina Biswakarma; Vikram Talaulikar; Joyce C Harper (BMC, 2023)
Abstract Objectives To evaluate women's knowledge and attitudes towards the menopause by comparing three groups of women: perimenopause, post menopause and those women not in either the peri or post menopause (other). Methods A 35 question online survey was advertised on social media to evaluate women's attitudes and knowledge of the menopause. Three groups of women were compared: perimenopause, post menopause and those women not in either the peri or post menopause (other). Results Most women were completely uninformed or only had some knowledge of the menopause before the age of 40. Most women thought that the menopause should be taught at school, but over 80% had received no menopause education at school themselves. The most popular sources of menopause information were independent websites and friends. Perimenopausal women were significantly more likely than postmenopausal women to use online resources for menopause information. The perimenopausal and postmenopausal groups had more positive attitudes towards the menopause than the other group. 57.5% of postmenopausal women found the menopause difficult or very difficult. Most women were happy about no longer menstruating, although some expressed sadness regarding fertility loss. Conclusions Most women had limited knowledge and negative attitudes towards the menopause, leaving them unprepared to cope with the physical and psychological changes associated with this stage of life. Improved menopause education is required to improve quality of life during the menopausal transition and a most positive narrative of life postmenopause.